Entrepreneurial university strategies in the UK context: towards a research agenda. Issue 12 (12th June 2019) - Pickernell, David; Ishizaka, Alessio; Huang, Shuangfa; Senyard, Julienne
Abstract : Purpose: Prior research shows that universities differ in the knowledge exchange (KE) activities they pursue, but little is known about universities' strategies regarding their portfolio of KE activities. The purpose of this paper is to explore the KE strategy of UK universities in specific relation to their portfolio of KE activities with small- and medium-sized enterprises. Design/methodology/approach: Based on the 2015–2016 Higher Education Business and Community Interaction Survey data set, this study employs the Preference Ranking Organisation METHod for the Enrichment of Evaluations to assess the KE activities from 162 UK higher education institutions. Findings: The study reveals that entrepreneurial universities valorise university knowledge assets through five SME-focussed KE activities most beneficial to measuring the entrepreneurial university. It also uncovers four different archetypal categories (groupings) of universities based on their strategic focus of KE activities. Originality/value: This study contributes to the entrepreneurial university literature by considering universities' overall KE portfolio rather than examining individual KE activity in isolation. It provides a clearer understanding of universities' KE strategies that help define and delineate entrepreneurial universities regarding their range, focus and the combination of KE activities.